2020
DOI: 10.2478/rjim-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pancreatic cancer: a review for general clinicians

Abstract: Pancreatic cancer (PC) is an exceptionally lethal malignancy with increasing incidence and mortality worldwide. One of the principal challenges in the treatment of PC is that the diagnosis is usually made at a late stage when potentially curative surgical resection is no longer an option. General clinicians including internists and family physicians are well positioned to identify high-risk individuals and refer them to centers with expertise in PC screening and treatment where screening modalities can be empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies and has a dismal prognosis with an overall 5-year survival rate of less than 10% [ 3 ]. The only curative therapy for PDAC is early detection followed by surgical resection [ 5 ]. Hence, early detection is important in improving the prognosis and overall survival of patients with PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies and has a dismal prognosis with an overall 5-year survival rate of less than 10% [ 3 ]. The only curative therapy for PDAC is early detection followed by surgical resection [ 5 ]. Hence, early detection is important in improving the prognosis and overall survival of patients with PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Though EUS is now considered the most sensitive imaging modality for the detection of pancreatic lesions, Wiest et al [164], reported a sensitivity of 88-100%, a specificity of 63.4-94%, a positive predictive value (PPV) of 71.4-96.2%, and a negative (N) PV of 68.5-100% for MRI, that with MRCP has a sensitivity of 97.1-100%, a specificity of 81.8-88%, a PPV of 94.4-97%, and a NPV of 90-100%, similar to EUS, while a lower accuracy was reported for CT. CT sensitivity and specificity are correlated to detector numbers and study protocol [164]. The possibility to add EUS conventional protocol, elastography and/or contrast-enhanced ultrasound (CEUS) could improve the sensitivity of EUS for PC screening [165].…”
Section: Screening Modalitiesmentioning
confidence: 99%